Analisis Gangguan Hubung Singkat Pada Sistem Tenaga Listrik Di KSO Pertamina EP - GEO Cepu Indonesia Distrik 1 Kawengan Menggunakan Software ETAP 12.6 - Saputra, Very Bagus; , Ir. Jatmiko, M.T (2016)
Study of short circuit is important in planning the manufacture of electric power systems. Short circuit occurs when the phase conductor is connected directly to the neutral conductor. Because no such resistance electrical appliancesvthus the short circuit current flow is proufoundly big. To mitigate this, the analysis is necessary so that a large short circuit fault current flow in the system can be identified and protective equipment to be used can be determined. This study will be to analyze the three-phase short-circuit current, one phase to ground, two-phase and two phase to ground. Research began on the collection of data required for analysis. Then create a single line using ETAP Power Station 12.6 according to the data that has been obtained. Continued a single line so then do short circuit simulation to determine whether a single line that has been made is appropriate or not. If a single line is not appropriate then repaired again. After the simulation is done by varying the location of the short circuit interruption. That is near the source of plant, near the load, and between the generator and the load. The simulation results determine the short-circuit current three-phase, single phase to ground, two-phase and two phase to ground. Location disorder also affects a large short-circuit current occurs. The short circuit current is more bigger when the its location near with power plant.